Settlement-time curve calculation of soil-cement column and slab improved soft clay deposit - S. Pongsivasathit; P. Voottipruex; J.C. Chai (International Association of Lowland Technology, 2017)
The consolidation behavior of soft clayey deposit improved by a floating soil-column with a cement stabilized slab on the ground surface has been investigated by laboratory model test using a symmetric unite cell model and finite element analysis (FEA). The effects of thickness and undrained shear strength of slab on the relative penetration of column into surrounding soil were quantified. Based on the results, the method proposed Pongsivasathit et al. for calculating the settlement of a floating column improved soft subsoil has been modified. The main modification is the equation for calculating the value of Hc, which is the thickness of a soil layer at the bottom of the column improved zone. And in settlement calculation, Hc layer has been treated as an unimproved layer. The effectiveness of proposed method has been verified by comparing with the measurement results of field case histories and laboratory model tests.